Effect of proper oral rehabilitation on general health of mandibulectomy patients - Mustafa, Ammar A.; Abdul Majeed, Kais Raad; Mustafa, Nazih Shaban (Wiley Online Library, 2015)
Introduction Reduced oral aperture and mandibular opening are relatively common problems, which have a wide variety of causes [1]. Limited access to the oral cavity can be problematic for patients and dental professionals [2]. According to Glossary of Prosthodontics terms GPT [3], reduced oral aperture is defined as microstomia, which is a term used to describe any congenital or acquired reduction in the size of the oral opening that is severe enough to compromise esthetic, deglutition, nutrition, and quality of life [4]. The mandible is the key bone involved in face esthetic, mastication, and speech. Surgical resection of the mandible (known as a mandibulectomy) is often performed for tumors of the head and neck area, which should be followed by oral rehabilitation (i.e., occlusal adjustments and replacement of missing teeth and/or soft tissues, if involved) [5]. The treatment of oral tumors such as squamous cell carcinomas may require mandibular resection to secure adequate margins [6]. Segmental resection of the mandible leads to significant patient illness if not properly managed. Mandibulectomy can lead to loss of mandibular support to the teeth, inadequate mastication, impaired speech and disfigurement of the face [7].